Job Description Kejelasan Tanggung Jawab dan Aplikasinya Persfektif Hadist Nabi Muhammad SAW - Ramli L; Ambo Asse; Muhammad Yahya (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2024)
This article aims to find out the job description, clarity of responsibilities and application from the perspective of the hadith of the Prophet Muhammad SAW. Data is obtained from articles published through Google Scholar. Initially, the search was carried out using relevant keywords such as "job description", "job description in the perspective of the Prophet Muhammad SAW". Data from selected articles were then analyzed using a descriptive approach to describe key findings, identify patterns and trends, and summarize key conclusions from the reviewed literature. The results of the analysis show that with the job description, the activities carried out are in accordance with the responsibilities and cannot interfere with each other's duties, there is no overlap in the implementation of duties, and communication is well formed due to the existence of a good cooperative relationship between workers. In Islam, a job or position is a mandate that must be maintained properly, because behind the mandate there is accountability. Islam also teaches not to impose oneself on a job or position that is not one's expertise